Relationship between subclinical hypothyroidism and serum homocysteine concentration in premenopausal women. Issue 3 (2013) - Çolak, Ayfer Aydogdu; Avcı, Ramazan; Yener, Serkan; Kurtulmuş, Yusuf; Zengin, Mustafa Osman; Bozkurt, Ümit; Üstüner, Füsun
No abstract available